Minimal cut sets for transportation system - Mihova, Marija; Stojkovich, Natasha (My University, 2010)
One of the most significant problems in the analysis of the reliability of multi-state transportation systems is to find the minimal path and minimal cut vectors. For that purpose there are proposed several algorithms that use the minimal path and cut sets of such systems. In this paper we give an approach to determine the minimal cut vectors. This approach directly finds all minimal cut sets. Also we will give an optimization of the basic idea, as a result of which, we will not get a candidates for minimal path sets, which actually are not a minimal cut sets.